Allergies in dental care - Martinez Camus, Daniela Catalina (2020)
Dental staff and patients are exposed to numerous allergens in dental care, for this reason, this review aims to provide guidelines for the identification of allergens in the dental practice, describe the signs and symptoms of allergic reactions, and advise its treatment. Allergens include latex, metals, local anesthetics, endodontic materials, impression materials, and drugs. Dental allergens mainly cause type I and IV hypersensitivity reactions. In the diagnostic process, an anamnesis and a thorough clinical examination are required to identify the suspected allergen. In addition, complementary tests such as patch and puncture tests can be used. The dentist must recognize the signs and symptoms associated with allergic reactions, identify the cause and avoid exposure of the patient or dental personnel. In the event, that an allergic reaction occurs, its treatment will include elimination of the allergen, and the use of antihistamines and corticosteroids. If the case is an anaphylactic shock, epinephrine is the drug of choice. Dental professionals need to be prepared to identify and manage hypersensitivity reactions, and to refer the immunologist/allergist specialist if necessary.